PROSPEK PENGEMBANGAN AGROWISATA SEBAGAI WISATA ALTERNATIF DI DESA PELAGA - Ni Wayan Wahyu Astuti (Soshum: Jurnal Sosial dan Humaniora, 2013)
Development of the tourism sector in the province of Bali need to be developed in accordance with the conditions, potential and resources owned by each district in Bali. Tourism in fairly rapid growth requires new breakthroughs in anticipation of the saturation that may occur on tourists. Then came the development of tourism opportunities that promote the preservation of the natural environment in order to prevent destruction and/or environmental pollution caused by tourism activities, better known as the " Back to Nature ". Involvement as an alternative tourism attraction will provide an option for international travelers and domestic tourists to enjoy and extend their stay in Bali in particular and Indonesia in general. One of agrotourism development in Bali Bagus Agro Pelaga done by adding, promote or improve the necessary facilities and manage them well so crowded so interesting and beneficial to the government, investors and local communities. Development of the Agro done gradually and in accordance with the concept of development in the area of tourism development does not rule out the required resource sustainability for next generations..